2023
DOI: 10.3390/genes14061280
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Pan-Cancer Analysis of the Potential Biological Functions and Prognosis Values of RICTOR

Abstract: The importance of the network defined by phosphatidylinositol-3-kinase (PI3K), AKT and mammalian target of rapamycin (mTOR) downstream of Receptor Tyrosine Kinase (RTK) has been recognized for many years. However, the central role of RICTOR (rapamycin-insensitive companion of mTOR) in this pathway has only recently come to light. The function of RICTOR in pan-cancer still needs to be systematically elucidated. In this study, we examined RICTOR’s molecular characteristics and clinical prognostic value by pan-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…This discovery seems at odds with the well-established role of mTORC2 signaling in promoting cell growth and survival across various pathophysiological contexts [ 14 , 38 – 40 ], including melanoma progression [ 38 , 39 ]. However, our findings align with emerging evidence indicating tumor suppressive functions for mTORC2 in different settings [ 15 , 16 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…This discovery seems at odds with the well-established role of mTORC2 signaling in promoting cell growth and survival across various pathophysiological contexts [ 14 , 38 – 40 ], including melanoma progression [ 38 , 39 ]. However, our findings align with emerging evidence indicating tumor suppressive functions for mTORC2 in different settings [ 15 , 16 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated both RICTOR amplification and Rictor overexpression in different types of cancer, including lung cancer [9,17,[42][43][44][45][46][47]. Moreover, both RICTOR amplification and Rictor overexpression have been identified to be associated with poor prognosis and shorter survival [17,28,48]. In addition to amplification, a few other mechanisms (e.g., glucose-dependent acetylation or DNA methylation) have also been described to regulate Rictor expression and, therefore, mTORC2 activation [48,49].…”
Section: Rictor-mtor Association-the Mtorc2 Protein Complex and Its F...mentioning
confidence: 99%
“…Moreover, both RICTOR amplification and Rictor overexpression have been identified to be associated with poor prognosis and shorter survival [17,28,48]. In addition to amplification, a few other mechanisms (e.g., glucose-dependent acetylation or DNA methylation) have also been described to regulate Rictor expression and, therefore, mTORC2 activation [48,49]. However, further investigations are needed to reveal the exact role of these processes.…”
Section: Rictor-mtor Association-the Mtorc2 Protein Complex and Its F...mentioning
confidence: 99%